2013
DOI: 10.1038/tp.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neuroimaging evidence for overreliance on habit learning in alcohol-dependent patients

Abstract: Substance dependence is characterized by compulsive drug-taking despite negative consequences. Animal research suggests an underlying imbalance between goal-directed and habitual action control with chronic drug use. However, this imbalance, and its associated neurophysiological mechanisms, has not yet been experimentally investigated in human drug abusers. The aim of the present study therefore was to assess the balance between goal-directed and habit-based learning and its neural correlates in abstinent alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
231
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(251 citation statements)
references
References 63 publications
14
231
1
1
Order By: Relevance
“…Hence these findings need to be treated with caution and require replication. Furthermore, while animal studies have convincingly shown a shift towards model-free choices in addiction, and indeed with alcohol [4,5,7], there have been only limited investigations to substantiate this in humans so far [23,27]. One reason may be that it has been difficult to measure these two systems in humans and often has required rather laborious tasks involving extended training [71,72].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence these findings need to be treated with caution and require replication. Furthermore, while animal studies have convincingly shown a shift towards model-free choices in addiction, and indeed with alcohol [4,5,7], there have been only limited investigations to substantiate this in humans so far [23,27]. One reason may be that it has been difficult to measure these two systems in humans and often has required rather laborious tasks involving extended training [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…This may hint at an effect of alcohol on more general measures of cognitive functioning [58]. Goal-directed control has also been associated with prefrontal areas [27,59,60]. This raises the question of whether drugs directly affect goal-directed choices or do so only secondarily to their effects on other, more general cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, decreased vmPFC activity has been observed in alcoholics showing elevated propensity toward habitual behavior (Sjoerds et al 2013). Others have suggested that the human vmPFC may be involved in the suppression of irrelevant information, potentially by integrating information from separable components of limbic corticostriatal circuitry (Nieuwenhuis and Takashima 2011).…”
Section: Potential For Translation To the Human Disease Statementioning
confidence: 99%
“…After an outcome devaluation (e.g., through satiation), the MB system can change preferences quickly, but the MF system cannot. Individual variation in the balance between MB and MF decisions, with a shift toward MF and away from MB learning, is associated with addictive and impulsive traits in animals (Huys et al, 2014;Everitt & Robbins, 2005), and a bias has been reported in conditions such as addiction and obsessive-compulsive disorder where behavioral preferences persist against explicit desires (Voon et al, , 2015Gillan et al, 2011Gillan et al, , 2014Sebold et al, 2014;Sjoerds et al, 2013).…”
Section: Introductionmentioning
confidence: 99%